The effect of polypharmacy on healthcare services utilization in older adults with comorbidities: a retrospective cohort study - Doumat, George; Daher, Darine; Itani, Mira; Abdouni, Lina; El Asmar, Khalil; Assaf, Georges (BMC family practice, 2023)
Older adults are more prone to increasing comorbidities and polypharmacy. Polypharmacy is associated with inappropriate prescribing and an increased risk of adverse effects. This study examined the effect of polypharmacy in older adults on healthcare services utilization (HSU). It also explored the impact of different drug classes of polypharmacy including psychotropic, antihypertensive, and antidiabetic polypharmacy on HSU. This is a retrospective cohort study. Community-dwelling older adults aged ≥ 65 years were selected from the primary care patient cohort database of the ambulatory clinics of the Department of Family Medicine at the American University of Beirut Medical Center. Concomitant use of 5 or more prescription medications was considered polypharmacy. Demographics, Charlson Comorbidity index (CCI), and HSU outcomes, including the rate of all-cause emergency department (ED) visits, rate of all-cause hospitalization, rate of ED visits for pneumonia, rate of hospitalization for pneumonia, and mortality were collected. Binomial logistic regression models were used to predict the rates of HSU outcomes. A total of 496 patients were analyzed. Comorbidities were present in all patients, with 22.8% (113) of patients having mild to moderate comorbidity and 77.2% (383) of patients having severe comorbidity. Patients with polypharmacy were more likely to have severe comorbidity compared to patients with no polypharmacy (72.3% vs. 27.7%, p = 0.001). Patients with polypharmacy were more likely to visit the ED for all causes as compared to patients without polypharmacy (40.6% vs. 31.4%, p = 0.05), and had a significantly higher rate of all-cause hospitalization (adjusted odds ratio aOR 1.66, 95 CI = 1.08-2.56, p = 0.022). Patients with psychotropic polypharmacy were more likely to be hospitalized due to pneumonia (crude odds ratio cOR 2.37, 95 CI = 1.03-5.46, p = 0.043), and to visit ED for Pneumonia (cOR 2.31, 95 CI = 1.00-5.31, p = 0.049). The association lost significance after adjustment. The increasing prevalence of polypharmacy amongst the geriatric population with comorbidity is associated with an increase in HSU outcomes. As such, frequent medication revisions in a holistic, multi-disciplinary approach are needed.